Diseño de una propuesta para el Mejoramiento Empresarial del Servicio Automotriz, para el Sector de Catambuco en Nariño - Medina Urbano, Francisco Javier (Universidad Antonio Nariño, 2024)
The provision of automotive service today has gained great importance within the global economy, not only in large cities where a large number of of means of transportation, including vehicles or automobiles, that become a means of transportation. sustenance for some and for others as a means of transportation and cargo; This also happens in areas rural areas where they have great potential for economic growth, and with the use of new technologies, their development is moving by leaps and bounds.